2019
DOI: 10.1111/odi.13145
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in gingivocrevicular fluid of rheumatoid arthritis patients: A review of the literature

Abstract: Objective Rheumatoid arthritis (RA) and periodontitis share several pathological features including bone and soft tissue destruction and high levels of circulating inflammatory proteins. Studies related to cytokines in the periodontal inflammatory exudate (gingivocrevicular fluid, GCF) of RA patients might provide insight into the association between periodontitis and RA. The aim of our study was to review the literature on cytokines in GCF of RA patients including the effect of anti‐rheumatic treatment with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…In contrast to the more restricted profiles in saliva and GCF, we found that RA patients had a broader range of mediators in serum and joints, particularly Th1 and innate immune mediators. Consistent with previous studies, 29,30 our patients had reduced levels of the anti‐inflammatory cytokine, IL‐10, in GCF. In contrast with our findings, a prior study by Miranda et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the more restricted profiles in saliva and GCF, we found that RA patients had a broader range of mediators in serum and joints, particularly Th1 and innate immune mediators. Consistent with previous studies, 29,30 our patients had reduced levels of the anti‐inflammatory cytokine, IL‐10, in GCF. In contrast with our findings, a prior study by Miranda et al.…”
Section: Discussionsupporting
confidence: 92%
“…In one study of 35 chronic RA patients, IL‐1β levels were elevated in saliva compared with those in healthy individuals (HIs), 27 while another study evaluating salivary TNF‐α levels in chronic RA patients did not find TNF‐α elevation 28 . Several studies of GCF in chronic RA patients, mainly those with periodontitis 29,30 revealed elevated levels of IL‐1β, TNF, MMP‐8, MMP‐9 and MMP‐13, and reduction in IL‐10, findings similar to those in non‐RA chronic periodontitis. GCF MMP‐8 and MMP‐9 levels in chronic RA patients with periodontitis tended to be even higher than in those with non‐RA chronic periodontitis 30 .…”
Section: Introductionmentioning
confidence: 91%
“…This reduction in DAS28 was not related to the PISA or the presence of other intra-oral pathologies, such as caries and peri-apical pathology. On the contrary, periodontal treatment in RA patients was shown to clearly improve DAS28 scores and ESR levels, while other systemic inflammatory markers, such as CRP, IL-6, and TNF, tended to decrease [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent literature reviews have summarized studies performed in GCF in RA patients on cytokines, chemokines, enzymes, and tissue breakdown products stratified for periodontitis 8,9 . There were inconclusive results as to levels of interleukin‐1β (IL‐1β) in periodontitis in RA as summarized from several cross‐sectional studies, and the same levels of interleukin‐4 (IL‐4) and interleukin‐10 (IL‐10) between RA patients, periodontitis, and periodontally healthy patients 8,9 . Matrix metalloproteinase‐8 (MMP‐8), MMP‐9, and tumor necrosis factor alpha (TNF‐α) levels were higher in periodontitis and in RA and MMP‐8 levels increased with the severity of periodontitis 8,9 .…”
Section: Introductionmentioning
confidence: 99%